Space case - Gibbs, Stuart, 1969- (Gibbs, Stuart, 1969- Moon Base Alpha novel., 2014)
"Dashiell Gibson, who lives on Moon Base Alpha, has to solve a murder of one of the moon's most prominent doctors"--